2017
DOI: 10.1123/ijsnem.2015-0345
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Exercise-Induced Oxidative Stress at Simulated Moderate Level Altitude vs. Sea Level in Trained Cyclists

Abstract: Page 1 of 9 However, these responses have not been monitored in endurance-trained cyclists at altitudes typically experienced while training. Endurance trained males (n = 12; mean (± SD) age: 28 ± 4 years, V O2max 63.7 ± 5.3 ml/kg/min) undertook two 75-min exercise trials at 70% relative V O2max; once in normoxia and once in hypobaric hypoxia, equivalent to 2000m above sea level (hypoxia). Blood samples were collected before, immediately after and 2 h postexercise to assess plasma parameters of oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In the present study, expression of CAT was decreased after hypobaric hypoxia. Wadley et al also found changes in the expression of CAT in the serum in cyclists at altitude but an up-regulation and not a down-regulation [ 27 ]. This is in congruency to the results of Krzeszowlak et al who also found increased CAT activity after a nine-day exposure to high-altitude conditions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, expression of CAT was decreased after hypobaric hypoxia. Wadley et al also found changes in the expression of CAT in the serum in cyclists at altitude but an up-regulation and not a down-regulation [ 27 ]. This is in congruency to the results of Krzeszowlak et al who also found increased CAT activity after a nine-day exposure to high-altitude conditions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The excessive overproduction of RONS, in excess of the endogenous antioxidant defense systems, can cause damage to lipids, proteins and DNA which may impair cell and immune function, resulting in delayed post-exercise recovery [74]. Both acute [75, 76] and chronic exposure to hypoxia [72, 77, 78] augments oxidative stress in well-trained athletes, while reduced antioxidant capacity may persist for up to 2 weeks following altitude training [79]. Interestingly, normobaric hypoxia appears to produce a larger increase in oxidative stress than hypobaric hypoxia [80], while a recent study in a team sport setting showed no impact of intermittent hypoxia on biomarkers of oxidative stress [81].…”
Section: Micronutrient Considerations To Optimize Adaptation To Altitudementioning
confidence: 99%
“…McGinnis et al [50] simulated altitude in an environmental chamber and they found an increase in LPE after cycling at 60% at an altitude of 3000 m in comparison to 975 m of altitude. Recently, Wadley et al [51] evaluated the independent effect on OS of acute exercise and hypoxic exposure comparing two different training habits: sea level and 2000 m above sea level. At the same exercise intensity and immediately post-exercise, at high level, there is an increase in plasma CA activity and total protein carbonylation (PC) content in comparison to sea level and the authors reported a decrease in PC when the exercise was performed in normoxia.…”
Section: Redox Homeostasis and Oxidative Stress In Sportsmentioning
confidence: 99%